Tailoring the dosing schedule of nab-paclitaxel in metastatic breast cancer according to patient and disease characteristics: Recommendations from a panel of experts. (March 2016) - Arpino, G.; Marmé, F.; Cortés, J.; Ricevuto, E.; Leonard, R.; Llombart-Cussac, A.
Abstract: The choice of chemotherapy for patients with metastatic breast cancer (MBC) depends on disease- and patient-related factors, but there is little guidance on dosing modifications for patients unable to receive the licensed dose. Nab -paclitaxel is a solvent-free form of paclitaxel that uses albumin as a drug carrier and exploits endogenous albumin transport pathways to achieve enhanced drug targeting and tumour penetration with reduced toxicity. It is approved for use at a dose of 260 mg/m 2 every three weeks in adults who have failed first-line treatment for MBC and for whom standard anthracycline-based therapy is not indicated. Emerging data suggest that weekly dosing schedules of nab -paclitaxel may provide clinical benefit in some patients, but the utility of these alternative dosing schedules remains unclear. A panel of breast cancer experts convened to review available literature for nab -paclitaxel in MBC and, taking into account their clinical experience, recommended that alternative dosing schedules may be considered according to the aggressiveness of disease and patient condition as follows: 125 mg/m 2 QW 3/4 (aggressive disease and fit), 100 mg/m 2 QW 3/4 (aggressive or indolent disease and unfit). All dosing schedules were considered acceptable for fit patients with indolent disease. These recommendations are based on current evidence, and emerging data from ongoing trials may reinforce or modify the recommendations provided.